Использование метода перколяционной экстракции для извлечения липидов из вторичных продуктов масложировой промышленности - Омельченко, Юлия Евгеньевна; Демидов, Игорь Николаевич (НТУ "ХПИ", 2015)
Воскоподобные вещества являются ценным продуктом и сырьем для многих отраслей промышленности. Существующие способы получения восков имеют ряд недостатков, таких как значительные энергетические затраты, большой расход растворителя или образование дополнительных отходов. В статье представлены результаты исследований выделения липидов из отработанного фильтрующего порошка (зажиренный перлит) с последующим выделением воскоподобных веществ методом перколяционной экстракции.

Waxen substances are a valuable product and raw material for many manufacture branches. The existing methods of obtaining waxes have a number of disadvantages, namely essential energy costs and solvent consumption as well as additional wastes buildup. The research revealed efficient conditions under which neutral lipids and waxen substances are recovered from filter powder (perlite containing fats). The optimum relationship between the mixture components (filter powder and fusel-oil) was defined. The chosen percolation extraction approach proved its efficiency because the miscella became more concentrated and the solvent flow significantly reduced. The oil content of the filter powder made up less than 1% that provides with the opportunity to recommend it to be recycled at the oil winterization stage. Moreover, this percolation extraction method allowed recovery of more than 98% of waxen substances from the used filter powder. This perlite regeneration approach provides with the opportunities to return the adsorbent to the stage of waxen substances filtration, utilize neutral lipids for technical and feeding purposes, and recover a valuable product - waxen substances used in different fields of national economy.
The using percolation extraction for recovery of lipids from the secondary products of oil industry
Keywords: воскоподобные вещества; фильтрующий порошок; гексан; сивушное масло; waxen substances; filter powder; fusel-oil